Effects of the modifier types to thermal, mechanical and barrier properties of polylactic acid/modified nanoclay nanocomposite - Abu Hannifa, Abdullah (2014)
Polylactic acid (PLA) is a biodegradable polymer, derived from renewable sources, having either a semi-crystalline or amorphous structure. These characteristics make PLA an excellent candidate for food packaging. However, it has many weaknesses such as poor thermal properties, brittle in tensile behaviour, and limited water barrier properties. The introduction of nanoclay leads to the significant improvement of the mechanical, barrier and thermal properties to the samples provided that the clay platelets are well dispersed in the PLA matrix. In this work, the focus were on the modification of the nanoclay using three types of modifier namely CU, where the nanoclay was modified with Copper (II) Chloride, TEA, where the nanocolay was modified with triethylamine and TEOS, where there nanoclay was modified with Cocamidopropyl Betaine to assist the improvement of the properties. Upon characterising the modified nanoclay using X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM), increased of d-spacing of the modified nanoclays up to 39.9Å has been seen confirming the success of the modification process. The fabrications of the nanocomposite films were performed by solution mixing method using dichloromethane as solvent creating nanocomposite samples using those three modified nanoclay and unmodified clay namely TEA, CU, TEOS and NA with 1, 2, and 3 wt% nanoclay. The nomenclatures of the samples were given by the name of modified nanoclay followed by the number of percent clay loading. The thermal properties of the films were tested on two areas that are thermal stability and melting temperature using Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). The results for thermal stability demonstrated both improvement and deterioration of thermal behaviour by knowing the values of the offset temperature. Increase in thermal degradation temperature up to 8.4% was demonstrated for TEA2 and 5.2% decreased by CU1. However, there was no significant change in the melting temperature, which 0.68% improvement was obtained in TEA2 and decrement of 1.38% of melting temperature for CU2 nanocomposite. All nanocomposite samples have shown improvement in water barrier property. Using a modified version of ASTM E96/E96M-12 wet cup test, the permeance value of TEA3 has shown the greatest improvement by exhibiting 44% less permeance. Universal testing machine has been used to perform the tensile test. In the study of mechanical properties, the most improved tensile stress is NA1 because 24% increment in tensile strength has been demonstrated. The most decreased tensile strength belongs to NA3 with a decrement of 51.5%. For the Young’s modulus value, the most increased value was NA2 that has shown increment of 35% and the most decreased Young’s modulus value was TEA1 with a decrement of 46%. With these results, it has been understood that different properties of nanocomposite have been greatly improved and some were even deteriorated by adding certain type of nanoclay with an optimum amount of filler. The most favoured nanocomposite in this study was TEA2 that has shown improvement in all properties tested.